Student Voices regarding Practical Instruction in a Solar Energy Course indicates Student Satisfaction - Hertzog, Pierre E; Swart, Arthur J (African Engineering Education Association Conference, CUT, FS., 2016)
Within higher education, student voices or perceptions are useful in measuring effective instruction and are important to evaluate the nature and quality of educational interventions. Student voices are often considered in determining whether student academic satisfaction exists with regard to the quality of engineering education being offered. The question thus arises “What does student voices say regarding practical instruction offered in a Solar Energy course at the Central University of Technology in South Africa”. Research has shown that voices of undergraduate engineering students indicated that they really enjoy practical work scheduled in a laboratory, thereby indicating a measure of student satisfaction. However, this was reported on only for students in an electronic communications course, with fewer results published for undergraduate engineering students in other disciplines at a university of technology. The purpose of this paper is to consider student voices regarding practical instruction offered in a Solar Energy course at a university of technology. An exploratory case study is employed along with descriptive statistics for the quantitative data relating to the student voices. An electronic response system was used in a classroom environment to listen to student voices relating to the practical work done in the laboratory. These student voices did confirm that many of the students felt that the practical work was beneficial, relevant and practical in helping them apply new knowledge in solving engineering problems, resulting in a measure of student satisfaction. This has the potential to result in the retention of the best and brightest students from among these participants for future postgraduate studies which will most likely involve more intensive laboratory work!
Published Conference Proceedings
Keywords: Solar energy; student voices; learning outcomes; graduate attributes